Find the value of ( 1 1 + 1 + 2 1 + 1 + 2 + 3 1 + 1 + 2 + 3 + 4 1 + 1 + 2 + 3 + 4 + 5 1 + … ) 2
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution! Alternatively, we can just evaluate the sum inside of the parentheses, and then square it.
Using the Sum of n, n², or n³ , we know that 1 + 2 + … + n = 2 n ( n + 1 ) , so the sum is k = 1 ∑ ∞ k ( k + 1 ) 2 .
Using Partial Fractions , we can write this as k = 1 ∑ ∞ k 2 − k − 1 2 .
This is a Telescoping Series - Sum , and all the terms cancel except for 1 2 = 2 , so the sum is 2. Thus, our answer is 2 2 = 4 .
Problem Loading...
Note Loading...
Set Loading...
( 1 1 + 1 + 2 1 + 1 + 2 + 3 1 + 1 + 2 + 3 + 4 1 + . . . ) 2 = ( 1 1 + 3 1 + 6 1 + 1 0 1 + . . . ) 2 = [ 1 1 + 2 ( 6 1 + 1 2 1 + 2 0 1 + . . . ) ] 2 = [ 1 + 2 ( 2 ⋅ 3 1 + 3 ⋅ 4 1 + 4 ⋅ 5 1 + . . . ) ] 2 = [ 1 + 2 ( 2 1 − 3 1 + 3 1 − 4 1 + 4 1 − 5 1 + . . . ) ] 2 = [ 1 + 2 ( 2 1 ) ] 2 = ( 1 + 1 ) 2 = 4